Is SGSH heterozygosity a risk factor for early‐onset neurodegenerative disease?. Issue 3 (25th January 2021) - Douglass, Meghan L.; Beard, Helen; Shoubridge, Andrew; Nazri, Nazzmer; King, Barbara; Trim, Paul J.; Duplock, Stephen K.; Snel, Marten F.; Hopwood, John J.; Hemsley, Kim M.
Abstract: Lysosomal dysfunction may be an important factor in the pathogenesis of neurodegenerative disorders such as Parkinson's disease (PD). Heterozygous mutations in the gene encoding the lysosomal enzyme glucocerebrosidase ( GBA1 ) have been found in PD patients, and some but not all mutations in other lysosomal enzyme genes, for example, NPC1 and MCOLN1 have been associated with PD. We have examined the behaviour and brain structure of mice carrying a D31N mutation in the sulphamidase ( Sgsh ) gene which encodes a lysosomal sulphatase. Female heterozygotes and wildtype mice aged 12‐, 15‐, 18‐ and 21‐months of age underwent motor phenotyping and the brain was comprehensively evaluated for disease‐associated lesions. Heterozygous mice exhibited impaired performance in the negative geotaxis test when compared with wildtype mice. Whilst the brain of Sgsh heterozygotes aged up to 21‐months did not exhibit any of the gross features of PD, Alzheimer's disease or the neurodegenerative lysosomal storage disorders, for example, loss of striatal dopamine, reduced GBA activity, α‐synuclein‐positive inclusions, perturbation of lipid synthesis, or cerebellar Purkinje cell drop‐out, we noted discrete structural aberrations in the dendritic tree of cortical pyramidal neurons in 21‐month old animals. The overt disease lesions and resultant phenotypic changes previously described in individuals with heterozygous mutations in lysosomal enzyme genes such as glucocerebrosidase may be enzyme dependent. By better understanding why deficiency in, or mutant forms of some but not all lysosomal proteins leads to heightened risk or earlier onset of classical neurodegenerative disorders, novel disease‐causing mechanisms may be identified.